2016
DOI: 10.1080/08039488.2016.1263683
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, and its relationship with cognitive and emotional functions in alcohol dependency

Abstract: Alcohol dependency has deleterious effects on empathy ability, and cognitive and emotional functions. Those impairments can improve with abstinence. Empathy ability has strong relationships with cognitive and emotional functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 27 publications
0
39
1
Order By: Relevance
“…Firstly, the sample consisted of Dutch male social drinkers, thereby, limiting our findings’ generalizability to women and individuals with alcohol use disorders. Previous research indicates gender differences in EA performance (Ickes et al 2000 ) and in response to alcohol consumption (Mumenthaler et al 1999 ), as well as reduced cognitive empathy in alcohol-dependent subjects (Castellano et al 2015 ; Bora and Zorlu 2016 ; Erol et al 2017 ). Nevertheless, further factors related to alcohol dependence remain to be investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, the sample consisted of Dutch male social drinkers, thereby, limiting our findings’ generalizability to women and individuals with alcohol use disorders. Previous research indicates gender differences in EA performance (Ickes et al 2000 ) and in response to alcohol consumption (Mumenthaler et al 1999 ), as well as reduced cognitive empathy in alcohol-dependent subjects (Castellano et al 2015 ; Bora and Zorlu 2016 ; Erol et al 2017 ). Nevertheless, further factors related to alcohol dependence remain to be investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Alterations and impairments in social cognition is a common feature of many psychiatric disorders and conditions [1,2,3,4]. For instance, schizophrenia and autism spectrum disorders (ASD) are neurodevelopmental disorders characterized by marked impairments in social cognition, including theory of mind (ToM) deficits, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…High-functioning autism is one of several neuro-psychiatric functional impairments. People who are diagnosed with such are described as having limitations in the areas of social cognition [21][22][23][24][25][26][27][28][29][30] and empathy [31][32][33][34][35]. Research has also identified a lack of enterprise and an inability to take the initiative amongst people who have been diagnosed with high-functioning autism [36,37], as well as a limited ability to make plans and to be flexible [24].…”
Section: High-functioning Autismmentioning
confidence: 99%